Antimicrobial Resistance of Helicobacter pylori Isolates in Korea - Eun Jeong Gong; Ji Yong Ahn (The Korean Journal of Helicobacter and Upper Gastrointestinal Research)
Antimicrobial resistance is a growing problem in the eradication of Helicobacter pylori. A combination therapy with proton pump inhibitor, clarithromycin, and amoxicillin is recommended as the first-line treatment regimen in Korea. However, the eradication rate with a standard triple therapy has been unsatisfactory in the last decade, and one of the main reasons for treatment failure is the increasing prevalence of strains resistant to antimicrobials. Therefore, comprehensive and detailed information on antimicrobial resistance is mandatory to optimize the strategy of eradication treatment. The antimicrobial resistance of H. pylori is reported to vary according to study population, geographical region, and test methods. In this review, the prevalence of antimicrobial resistance of H. pylori isolates in Korea is summarized on the basis of recent studies.